Quenching nematicon fluctuations via photo-stabilization - Karimi, Nazanin; Alberucci, Alessandro; Virkki, Matti; Priimagi, Arri; Kauranen, Martti; Assanto, Gaetano (Photonics Letters of Poland, 2016)
Light localization into optical spatial solitons can be achieved by launching optical beams in nonlocal nonlinear nematic liquid crystals. Such solitons often undergo undesired fluctuations of their trajectories. We demonstrate that partial polymerization in monoacrylate-doped nematic liquid crystals is effective in quenching such fluctuations in transverse space. Full Text: PDF References G. Assanto, B. Svensson, D. Kuchibhatla, U.J. Gibson, C.T. Seaton, G.I. Stegeman, "Prism coupling into ZnS waveguides: a classic example of a nonlinear coupler", Opt. Lett. 11, 644 (1986). CrossRef G.I. Stegeman, G. Assanto, R. Zanoni, C.T. Seaton, E. Garmire, A.A. Maradudin, R. Reinisch, G. Vitrant, "Bistability and switching in nonlinear prism coupling", Appl. Phys. Lett. 52(11), 869 (1988). CrossRef G. Vitrant, R. Reinisch, J.Cl. Paumier, G. Assanto, G.I. Stegeman, "Nonlinear prism coupling with nonlocality", Opt. Lett. 14(16), 898 (1989). CrossRef G. Assanto, G.I. Stegeman, "Optical bistability in nonlocally nonlinear periodic structures", Appl. Phys. Lett. 56(23), 2285 (1990). CrossRef G.I. Stegeman, M. Segev, "Optical Spatial Solitons and Their Interactions: Universality and Diversity", Science 286(5444), 1518 (1999). CrossRef G. Assanto, M. Peccianti, "Spatial solitons in nematic liquid crystals", IEEE J. Quantum Electron. 39(1), 13 (2003). CrossRef D. Suter, T. Blasberg, "Stabilization of transverse solitary waves by a nonlocal response of the nonlinear medium", Phys. Rev. A 48, 4583 (1993). CrossRef W. Królikowski, O. Bang, "Solitons in nonlocal nonlinear media: Exact solutions", Phys. Rev. E 63, 016610 (2000). CrossRef C. Conti, M. Peccianti, G. Assanto, "Route to Nonlocality and Observation of Accessible Solitons", Phys. Rev. Lett. 91(7), 073901 (2003). CrossRef J.H. Marburger, E. Dawes, "Dynamical Formation of a Small-Scale Filament", Phys. Rev. Lett. 21, 556 (1968). CrossRef M. Peccianti, K.A. Brzdąkiewicz, G. Assanto, "Nonlocal spatial soliton interactions in nematic liquid crystals", Opt. Lett. 27(16), 1460 (2002). CrossRef C. Rotschild, B. Alfassi, O. Cohen, M. Segev, "Long-range interactions between optical solitons", Nature Phys. 2, 769 (2006). CrossRef W. Krolikowski, O. Bang, J.J. Rasmussen, J. Wyller, "Modulational instability in nonlocal nonlinear Kerr media", Phys. Rev. E 64, 016612 (2001). CrossRef M. Peccianti, C. Conti, G. Assanto, "Optical modulational instability in a nonlocal medium", Phys. Rev. E 68, R025602 (2003). CrossRef O. Cohen, H. Buljan, T. Schwartz, J.W. Fleischer, M. Segev, "Incoherent solitons in instantaneous nonlocal nonlinear media", Phys. Rev. E 73, 015601R (2006). CrossRef M. Peccianti, G. Assanto, "Incoherent spatial solitary waves in nematic liquid crystals", Opt. Lett. 26(22), 1791 (2001). CrossRef A.W. Snyder, D.J. Mitchell, "Accessible Solitons", Science 276, 1538 (1997). CrossRef C. Conti, M. Peccianti, G. Assanto, "Observation of Optical Spatial Solitons in a Highly Nonlocal Medium", Phys. Rev. Lett. 92(11), 113902 (2004). CrossRef I.B. Burgess, M. Peccianti, G. Assanto, R. Morandotti, "Accessible Light Bullets via Synergetic Nonlinearities", Phys. Rev. Lett. 102, 203903 (2009). CrossRef P.G. de Gennes, J. Prost, The Physics of Liquid Crystals (Oxford Science Publications, Clarendon Press, 2nd edition, 1993). I.C. Khoo, Liquid Crystals: Physical Properties and Nonlinear Optical Phenomena (Wiley, New York, 1995). M. Peccianti, G. Assanto, "Nematicons", Phys. Rep. 516, 147 (2012). CrossRef A. Piccardi, A. Alberucci, G. Assanto, "Sub-milliwatt dissipative nematicons and spontaneous light emission in dye-doped nematic liquid crystals", Electron. Lett. 46(11), 790 (2010). CrossRef A. Piccardi, A. Alberucci, G. Assanto, "Self-Turning Self-Confined Light Beams in Guest-Host Media", Phys. Rev. Lett. 104, 213904 (2010). CrossRef J. Beeckman, K. Neyts, X. Hutsebaut, C. Cambournac, M. Haelterman, "Time dependence of soliton formation in planar cells of nematic liquid crystals", IEEE J. Quantum Electron. 41(5), 735 (2005). CrossRef E. Braun, L.P. Faucheux, A. Libchaber, "Strong self-focusing in nematic liquid crystals", Phys. Rev. A 48, 611 (1993). CrossRef T. Wolinski, Private communication. M. Peccianti, G. Assanto, "Signal readdressing by steering of spatial solitons in bulk nematic liquid crystals", Opt. Lett. 26(21), 1690 (2001). CrossRef A. Pasquazi, A. Alberucci, M. Peccianti, G. Assanto, "Signal processing by opto-optical interactions between self-localized and free propagating beams in liquid crystals", Appl. Phys. Lett. 87, 261104 (2005). CrossRef J.F. Henninot, J.F. Blach, M. Warenghem, "The investigation of an electrically stabilized optical spatial soliton induced in a nematic liquid crystal", J. Opt. A: Pure Appl. Opt. 10, 085104 (2008). CrossRef A. Piccardi, Private communication. U. Laudyn, M. Karpierz, Private communication. J.F. Blach, J.F. Henninot, M. Petit, A. Daoudi, M. Warenghem, "Observation of spatial optical solitons launched in biased and bias-free polymer-stabilized nematics", J. Opt. Soc. Am. B 5, 1122 (2007). CrossRef Y. Aihara, M. Kinoshita, J. Wang, J.I. Mamiya, A. Priimagi, A. Shishido, "Polymer Stabilization Enhances the Orientational Optical Nonlinearity of Oligothiophene-Doped Nematic Liquid Crystals", Adv. Opt. Mat. 1(11), 787 (2013). CrossRef J. Wang, Y. Aihara, M. Kinoshita, J.I. Mamiya, A. Priimagi, A. Shishido, "Laser-pointer-induced self-focusing effect in hybrid-aligned dye-doped liquid crystals", Sci. Rep. 5, 9890 (2015). CrossRef M. Peccianti, A. Fratalocchi, G. Assanto, "Transverse dynamics of nematicons", Opt. Express 12(26), 6524 (2004). CrossRef